If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -9 = 3 Reorder the terms: -9 + 3z = 3 Solving -9 + 3z = 3 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3z = 3 + 9 Combine like terms: -9 + 9 = 0 0 + 3z = 3 + 9 3z = 3 + 9 Combine like terms: 3 + 9 = 12 3z = 12 Divide each side by '3'. z = 4 Simplifying z = 4
| -2x+6=16 | | 7p=35 | | (x-5)(x-6)=6 | | 4x-7=7x-5 | | x^4-17x^2+52=0 | | 3a-15=-6 | | 3y/2=-6 | | 4x+20=53-2x | | y=7x^2-x+11 | | V^2-2v=4v+40 | | 17=(3x) | | 5x/6=30 | | 0.2x=10 | | 6x-18+4y-20=170 | | 8b+3-10b=2(b-2)+3 | | -3x+-7=-22 | | 2x-2-12=3x-3 | | 6gh-15h+10-4g= | | 12x-4=13x-5 | | x^3-20x^2+96x=0 | | -x-4x-7=-2x+5 | | -10-3b=3b+2(-8b-5) | | 6g+2gh+5h+15= | | x(x+-6)=40 | | 40=5x-15 | | 8.4m-0.7-8m=0.22 | | 7x+10=2x-10 | | 2gh+5h-20-8g= | | 4(9.7-8.1)=4(9.7)-4(8.1) | | 5/6(9+2x)=40 | | -.5-1=15 | | 2gh-12h-5g+30= |